The Influence Of Culture, Education, And Entrepreneurial Innovation On Entrepreneurial Intention With Entrepreneurial Mindset As Intervening Variable On Management And Business Administration Students Class Of 2020 - Rizki Aditya; Sisca Eka Fitria (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The study aims to examining the connections among entrepreneurial culture, education, innovation on entrepreneurial intention with entrepreneurial mindset as intervening variable. Questionnaire data are distributed to 102 students from business management and business administration class of 2020 Telkom University who enrolled in small startup business development course for business management and entrepreneurship for business admnistration students, which was taken using snowball sampling methods with a helps from SmartPLS 3. The findings reveal that the the entrepreneurial culture significantly impacts entrepreneurial intention, mindset, and education, while entrepreneurial education has positive influence to entrepreneurial mindset and innovation. Furthermore, entrepreneurial innovation influenced both entrepreneurial mindset and intention. The study also confirmed the direct effects of entrepreneurial mindset to entrepreneurial intention as the final hypothesis.